Komunikasi Matematis dalam Pembelajaran Matematika Berbasis Permainan Tradisional: Systematic Literature Review pada Budaya Nusantara - St. Nur Khalifah Ali Ali; Suradi; Rosidah (Mandalika Mathematics and Educations Journal, 2025)
Mathematical communication skills are an essential competency in 21st century mathematics learning. Traditional approaches, which are generally abstract and lack context, are often a barrier to their development. This study aims to systematically examine various studies related to mathematical communication in traditional game-based mathematics learning in the cultural context of the archipelago. The method used is Systematic Literature Review (SLR) with PRISMA guidelines, as many as 15 articles published in 2020–2025 obtained from the selection of Google Scholar, ERIC, and Dimensions databases. The results of the study analysis showed that traditional games such as engklek, congklak, and marbles were most often used in learning and were proven to be effective in improving students' mathematical communication both verbally and in writing. This approach also contributes to increased learning motivation, concept understanding, and character building. These findings support the relevance of ethnomathematical approaches that link mathematics to local cultural practices. It was also found that learning mathematics that integrates traditional games not only strengthens academic competence, but also fosters an appreciation of contextual and meaningful local wisdom for Indonesian students.